PERJANJIAN INTERNASIONAL OLEH DAERAH SEBAGAI KEWENANGAN OTONOMI DAERAH - Noer Indriyati (Faculty of Law, Universitas Jenderal Soedirman, 2010)
Law number 32 year 2004 on Regional Government suggests need to do adjustment authority implementation Foreign Relations and Cooperation. Along with the entry into force of the regional autonomy act, the policy of foreign relations and diplomacy by the Central Government, among others, also aimed at empowering and promoting regional potentials. The freedom to conduct foreign relations and cooperation, did not rule on the future more increased in line with the will of Autonomous District and the City to obtain added value for the Autonomous Region concerned. The mechanism of cooperation carried out in consultation with and coordination of the Ministry.Keywords: treaty, sister’s city and sister’s province